2009
DOI: 10.1063/1.3123810
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel conductance switching in organic memory devices based on AlQ3 and Al/Al2O3 core-shell nanoparticles

Abstract: Multilevel conductance switching in organic memory devices based on AlQ3 and Al/Al2O3 core-shell nanoparticles is demonstrated. The effect of middle Al layer thickness and the size of the nanoparticles on device performance are investigated. The high-resolution transmission electron micrographs revealed the formation of core-shell nanoparticles. The device has shown a series of conductance states. These states are nonvolatile in nature and can be accessed by applying proper programming voltage above a threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…When probed under a 'read voltage', the high-state returned a higher current as compared to that from a device in its low-conducting state. Such an experiment to determine retention time of a memory device, commonly known as read-only memory (ROM) application [3,5,8], has been carried out for more than 1 h. Under a prolonged period of operation, the difference between currents under the 'read voltage' for the high-and low-states started to diminish. Similarly, if the voltage is looped for more than a 100 cycles, the device starts to exhibit a reminiscent effect with a closure of the hysteresis in I-V characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When probed under a 'read voltage', the high-state returned a higher current as compared to that from a device in its low-conducting state. Such an experiment to determine retention time of a memory device, commonly known as read-only memory (ROM) application [3,5,8], has been carried out for more than 1 h. Under a prolonged period of operation, the difference between currents under the 'read voltage' for the high-and low-states started to diminish. Similarly, if the voltage is looped for more than a 100 cycles, the device starts to exhibit a reminiscent effect with a closure of the hysteresis in I-V characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that memory applications in such systems appear due to stable conductance-switching or electrical bistability [6,8]. More focus has been put forwarded on oxides and II-VI semiconducting quantum dots (than organic semiconductors [9,10] and metal nanoparticles) so that both optical and electrical properties can be utilized for the 'write' and 'read' processes of memory applications [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of nanoparticles have been used in OBDs, which include a metal nanoparticle, an inorganic oxide and a quantum dot [1][2][3][4][5][6]. Al and Au are the most common metal nanoparticles in OBDs [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have demonstrated multilevel conductance switching correlating closely with the NDR effect based on different organic materials [76][77][78][79][80]. In 2005, Majumdar et al [76] demonstrated a bistable device and WORM device merely by changing the concentration of fullerenes (C 60 ) in a polystyrene insulating matrix (PS:C 60 ), with both devices exhibiting the NDR effect.…”
Section: Multilevel Effect Of Two-terminal Organic Memory Devicesmentioning
confidence: 99%